2012
DOI: 10.5171/2012.786298
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Features of Patients with Dengue in Northeastern Region of India: A Retrospective Cross-Sectional Study during 2009-2011

Abstract: The incidence of fever cases of unknown origin has increased in Northeastern Region of India in recent years. We conducted passive surveillance and performed laboratory testing on suspected cases for the presence of dengue infection during 2009-2011. We estimated the incidence by applying age, sex and season adjusted dengue positivity. We identified 430 suspected cases of which 143 (33.3%) were found to be laboratory-confirmed dengue cases. Dengue transmission was found to occur in post-monsoon season (Septemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
7
16
4
Order By: Relevance
“….67%) were slightly higher than the rural (362, 46.65%) areas. Although previous studies from Gujarat & India showed that prevalence of dengue cases were much higher in urban areas; difference here in the present study is much less Madhulika Mistry et al, 2015;Durani et al, 2014;Patankar et al, 2014;Dutta et al, 2012;Khan et al, 2014. One reason for this can be natural demography of Kutch region where majority of population lives in rural areas as per Census 2011 data (Government of India, 2011 Census).…”
Section: Resultscontrasting
confidence: 54%
“….67%) were slightly higher than the rural (362, 46.65%) areas. Although previous studies from Gujarat & India showed that prevalence of dengue cases were much higher in urban areas; difference here in the present study is much less Madhulika Mistry et al, 2015;Durani et al, 2014;Patankar et al, 2014;Dutta et al, 2012;Khan et al, 2014. One reason for this can be natural demography of Kutch region where majority of population lives in rural areas as per Census 2011 data (Government of India, 2011 Census).…”
Section: Resultscontrasting
confidence: 54%
“…Majority of the patients were from Coimbatore and nearby districts. In relation to occupational profile our study differs from the study by Prafulla Datta et al where majority of the patients were blue collar workers (7). This was because their study population was from a rural location and ours is from an urban location.…”
Section: Fir1 Prevalence Of Dengue Infection With Agecontrasting
confidence: 54%
“…All serotypes were identified in the RT-PCR samples and DENV-1 was predominant (45.1%) [42]. Dual infections were also detected: DENV-1 and DENV-2 (3 cases); DENV-1 and DENV-3 (1 case); DENV-1 and DENV-4 (1 case); and DENV-2 and DENV-3 (3 cases) [42].…”
Section: Incidence Of Infectionmentioning
confidence: 93%
“…Of these, 89 were tested by RT-PCR and dengue was detected in 35: 27 instances of single serotype infection of DENV-3; 7 dual infections of DENV-1 and DENV-3; and one case of DENV-2 and DENV-3 mixed infection [36]. A retrospective surveillance study of 430 suspected dengue cases during 2009-2011 found 143 to be dengue positive (92 by IgM-capture ELISA and 51 by RT-PCR); these were collected from Assam (82), Meghalaya (35), Nagaland (15), Manipur (8) and Arunachal Pradesh (3) [42]. All serotypes were identified in the RT-PCR samples and DENV-1 was predominant (45.1%) [42].…”
Section: Incidence Of Infectionmentioning
confidence: 99%
See 1 more Smart Citation